DIFFERENT LIGHTING CONDITIONS AFFECT THE GERMINATION AND SEEDLING DEVELOPMENT OF TWO VARIETIES OF SHISO - Marques, Daniel Moncada Pereira; HÃ¼ther, Cristina Moll; Rocha, Nicole Pereira de Souza; Oliveira, Julia Ramos de; Ricardo, Rebecca de Andrade Klein; Rodrigues, NatÃ¡lia Fernandes; CorrÃªa, Gabriela Martins; Verde, Felipe Neves; Ferreira, Vitor Francisco; Santos, CaÃssa Machado Perucci Pereira dos; et al. (REVISTA DE AGRICULTURA, 2022)
Shiso (Perilla frutescens L.) is an Asian plant that contains properties that allow it to be used in both cooking and medicine. The present study set out to understand how different lighting conditions affect the germination and development of shiso seedlings of the purple and green varieties. Germination stabilization occurred 15 days after sowing (DAS), accounting for the environment with 70% shading 84 germinations of the purple variety and 34 germinations of the green variety. While, in the full sunshine treatment, germinations were much lower, however, the seedlings did not remain viable for monitoring the development of seedlings in full sunshine. After stabilization of germination, the following were evaluated: specific leaf area, diameter of the neck, height and number of leaves and but after 35 DAS there was a decrease in the production of biomass by both varieties.